A REVIEW OF MONKEYPOX DISEASE AND FUTURE TREATMENT OPTIONS - SHUKLA, AJAY KUMAR; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2023)
The Monkeypox virus (MPXV) causative agent for Monkeypox disease resembles a smallpox-like illness and can lead to a number of serious medical issues in humans. It is an enveloped double-stranded DNA virus and belongs to the Orthopoxvirus genus. Monkeypox cases have increased after the smallpox vaccine was no longer administered. Monkeypox did not really receive widespread attention until the 2003 US outbreak. The majority of monkeypox cases connected to the 2022 outbreak are being reported in nations surrounding Europe and in the western world. The neurological, respiratory, and gastrointestinal systems are all known to be impacted. There are currently no standardised or ideal guidelines for the clinical management of patients with monkeypox (MPX), especially in low-resource settings. Patient outcomes may also be poor and their illnesses may last a long time. The range of clinical manifestations, including complications and sequelae, as well as characteristics of the illness that may be indicators of illness severity and poor outcomes, must be better understood in order to improve care. Though more research is required before they can be used in an endemic setting, new therapeutics and vaccines offer hope for the treatment and prevention of monkeypox.